2015
DOI: 10.1260/1475-472x.14.1-2.193
|View full text |Cite
|
Sign up to set email alerts
|

Rudimentary Landing Gear Results at the 2012 BANC-II Airframe Noise Workshop

Abstract: The results of large-eddy and similar simulations and acoustic propagation calculations provided by six participants for the Rudimentary Landing Gear (RLG) category of the 2012 BANC-II workshop are analyzed and compared with experimental results. The general conclusion is that industrial accuracy remains elusive, and very significant differences exist between methods, so that the field needs more maturity, in addition to computing power. We present both blind comparisons from the workshop, and revised results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They found that the dominant noise sources were the tyre and the 30 sidebrace, compared to the cylinder, the axle, the torque link and the landing gear door. In a four-wheel Rudimentary Landing Gear (RLG) test, complex flow interactions were found between the upstream and downstream wheels [9,10], which might be a significant noise source. Liu et al…”
Section: Introductionmentioning
confidence: 99%
“…They found that the dominant noise sources were the tyre and the 30 sidebrace, compared to the cylinder, the axle, the torque link and the landing gear door. In a four-wheel Rudimentary Landing Gear (RLG) test, complex flow interactions were found between the upstream and downstream wheels [9,10], which might be a significant noise source. Liu et al…”
Section: Introductionmentioning
confidence: 99%
“…The authors believe that acoustic metamaterial research would benefit from benchmarking challenges, as are to be found in other domains 24 , 25 , so that advancements can be compared to one another. Average absorption in a frequency range, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Controversies over low-Mach-number and similar approximations linger. However, both for landing gear and high-lift devices, LES is quite successful at reproducing the turbulence itself and in particular, the wall pressure fluctuations (15) . Its potential is certain.…”
Section: Noise and Vibrationsmentioning
confidence: 99%